2015
DOI: 10.1161/atvbaha.115.305046
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylases and Cardiometabolic Diseases

Abstract: Cardiometabolic disease, emerging as a worldwide epidemic, is a combination of metabolic derangements leading to type 2 diabetes and cardiovascular disease. Genetic and environmental factors are linked through epigenetic mechanisms to the pathogenesis of cardiometabolic disease. Post-translational modifications of histone tails, including acetylation and deacetylation, epigenetically alter chromatin structure and dictate cell-specific gene expression patterns. The histone deacetylase (HDAC) family is comprised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 79 publications
1
18
0
Order By: Relevance
“…Two of the most interesting targets are PPAR isoforms PPARα and PPARγ, known to regulate lipid and glucose homeostasis through their coordinated activities in liver, muscle, and adipose tissue (45). Our findings of increased PPARα and PPARγ in tx-j mice correspond to a study indicating changes in PPARα and PPARγ in WD patients (27). Previous studies have shown PPARα increases with mild liver damage and decreases with moderate or greater liver damage, while PPARγ was increased in WD patients concomitantly with the progression of liver damage.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Two of the most interesting targets are PPAR isoforms PPARα and PPARγ, known to regulate lipid and glucose homeostasis through their coordinated activities in liver, muscle, and adipose tissue (45). Our findings of increased PPARα and PPARγ in tx-j mice correspond to a study indicating changes in PPARα and PPARγ in WD patients (27). Previous studies have shown PPARα increases with mild liver damage and decreases with moderate or greater liver damage, while PPARγ was increased in WD patients concomitantly with the progression of liver damage.…”
Section: Discussionsupporting
confidence: 83%
“…Peroxisome proliferator-activated receptor alpha (PPARα) and gamma (PPARγ) were selected from the TF gene analysis for further examination as they are key regulators of lipid metabolism. PPARα and PPARγ were also shown to be associated with steatosis and the antioxidant response, and exhibited decreased and increased protein levels, respectively, concomitant with liver damage severity in patients with WD (27). During an early stage of disease progression (9 weeks of age), Pparγ transcript levels were significantly higher in tx-j than C3H mice and Pparα transcript levels were reduced, but 8 days of HFD were associated with significantly increased Pparα expression (Figure 6C).…”
Section: Hdac5 Levels In Tx-j Mice Are Modulated By High Fat Dietary Interventionmentioning
confidence: 94%
“… 57 Sirtuin isoforms have also been shown to exert salubrious effects on fatty acid, amino acid, and glucose metabolism in mouse studies, which have led to clinical trials. 58 A search at clinicaltrials.gov with the keywords cardiovascular disease and epigenetics revealed 29 studies in the active or recently completed phase. These studies range in their employment of epigenetic measurements or interventions.…”
Section: Role Of Histone-modifying Enzymes In Cardiovascular Physiolomentioning
confidence: 99%
“…Previous studies in animal models have shown that reversible acetylation plays a crucial role in cardiovascular disorders, such as vascular diseases, heart failure, hypertension, arrhythmia, and angiogenesis. 75 HATs are classified into three major families: (1) GCN5-related N -acetyltransferases (GNATs), (2) p300/CREB-binding protein (p300/CBP), and (3) and the MOZ, Ybf2, Sas2, and Tip60 (MYST) family. 76 Histone acetylation increases gene expression by “opening” the chromatin structure.…”
Section: Main Textmentioning
confidence: 99%